PHYSICAL AND MECHANICAL CHARACTERIZATION OF PLANCHONELLA PACHYCARPA WOOD SPECIES FOR USE IN STRUCTURAL PURPOSE - Moura Aquino, Vinicius Borges de; Pereira de Freitas, Marcus Vinicius; Vasconcelos, Claudia Queiroz de; Boff Almeida, Joao Paulo; Arroyo, Felipe Nascimento; Castanheira Rodrigues, Edson Fernando; Christoforo, Andre Luis; Almeida, Diego Henrique de; Mello Silva, Sergio Augusto [UNESP]; Lopes Silva, Diogo Aparecido; Pinheiro, Roberto Vasconcelos; Rocco Lahr, Francisco Antonio (Slovak Forest Products Research Inst, 2021)
This research aimed to characterize the wood species Goiabao (Planchonella pachycarpa), following the precepts set forth in the Brazilian standard ABNT NBR 7190, as well as to evaluate the possibility of estimating physical and mechanical properties, using the analysis of variance (ANOVA) as a function of apparent density, and also to estimate the stiffness properties as a function of the respective strength property. The physical and mechanical properties were considered adequate for the use of this wood for structural purposes, being classified in class C40. According to the results of the regression models, it is possible to estimate the tensile strength parallel to the fibers as a function of the apparent density. It was also possible to estimate the longitudinal elastic modulus in the compression parallel to the fibers as a function of the compressive strength parallel to the fibers.
Keywords: Planchonella pachycarpa; apparent density; regression models; analysis of variance (ANOVA)